Security Functions Performed by Natural Elements in Traditional Malay Landscapes According to Malay Manuscript (Malay Literature, 2022)
Natural elements in a landscape refer to elements that are naturally present in the landscape. These elements contribute towards creating an aesthetic landscape ecology, which is a landscape that can fulfil the needs of its inhabitants, including security requirements. Traditional Malay landscapes are not behind in this aspect with their natural terrain, water sources, as well as flora and fauna. However, Malay communities today are largely unaware of Malay landscapes, which has resulted in an undefined vision of what Malay landscapes constitute of, and rendered Malay landscapes weaker compared to others. Moreover, studies on landscapes in Malay manuscripts still have not been receiving due attention despite traditional Malay society’s refined skills in choosing and building their own landscapes to the point that it has become a local wisdom. Following this, using library research and the application of the Landscape Aesthetic Theory, this article will identify natural elements in Malay landscapes and explain security elements in them based on the Sulalatus Salatin, Syair Siti Zubaidah Perang China and Hikayat Patani. This manuscript which has been recognised as a Full Registered Heritage and contains pertinent information regarding the subject at hand. There are three types of natural elements in traditional Malay landscapes based on the text, namely highlands, sources of water, and flora and fauna. All three natural elements are seen as security features that protect inhabitants from threats and danger. Therefore, it is hoped that the results of this study could showcase the local wisdom of Malay communities, and consequently become a guide for expanding studies on landscapes based on Malay manuscripts.Full text: PDF